Pengaruh Citra Koperasi, Kualitas Pelayanan, Dan Komunikasi Terhadap Loyalitas Nasabah Di Koperasi Rakyat Mandiri Abiansemal Kabupaten Badung - Sumariani, Ni Putu Ayu; Ayu Wimba, I Gusti (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Savings and loan cooperatives are economic institutions that are really needed to monitor because savings and loan cooperatives are a facility for people who want to develop a better life. Cooperative activity is participation that is suspected as a form of solving the various questions they face, therefore it is appropriate if a cooperative is in the economic system of an economic country. The formulation of the problem in this study: (1) the partial effect of cooperative image on customer loyalty at the Abiansemal People's Independent Cooperative; (2) the effect of service quality partially on customer loyalty at the Abiansemal People's Independent Cooperative; (3) the effect of partial communication on customer loyalty at the Abiansemal Mandiri People's Cooperative; (4) the effect of the cooperative image, service quality and communication simultaneously on customer loyalty at the Abiansemal People's Independent Cooperative. The purpose of this study was to determine the effect on the Citra cooperative, service quality and customer loyalty communication at the Abiansemal Independent People's Cooperative. This research was conducted at the Independent People's Cooperative Abiansemal Badung. The number of samples was determined by slovin as many as 84 respondents and selected samples using accidental sampling. The research instrument used is validity and reliability test and the analytical technique used is multiple linear regression, classical assumption test and hypothesis testing